The Role of Social Relationships in Reducing Depression Symptoms Among Elderly Residents in Social Institutions: A Descriptive Study - Gustya Tamansyah; Muryati Muryati; Vera FF; Zaenal Mutaqin; Dian Yuniar Syanti Rahayu; Rukman Rukman (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Depression is a common mental illness among older people. Earlier research has proven that poor social support is a major risk indicator for later-life depression. The present research has a goal of analyzing the relationship between support from friends and depressive symptoms among older people living at social institutions. A descriptive correlational design was used with a total sampling method. The population subjected to the research was 44 older people who lived at the Tresna Werdha Social Home Wisma Kartika Yatira. A structured questionnaire to rate support from friends was applied, containing validated items to assess both perceived and provided support. The results indicated that 25 respondents had moderate levels of support from their friends, whereas 19 had poor levels of support from their friends. Regarding depression, 23 respondents had no signs of depression, and 21 had slight signs of depression. There was a statistically significant relationship between support from their friends and depression (r = 0,722, p = 0.000). The evidence indicates that levels of support from their friends are linked with higher levels of depressive signs. From the findings, a proposal is made to adopt the SMB (Sharing Motivation Together) intervention—a peer-based intervention aimed at promoting mutual encouragement, emotional attachment, and activity among older persons at institutional settings.